Moralpolitik og marketing – Dansk Folkepartis brug af pressemeddelelser [Moral politics and marketing – The use of press releases by Dansk Folkeparti] - Orla Vigsø (MedieKultur: Journal of Media and Communication Research, 2011)
Dansk Folkeparti (the Danish People's Party) uses press releases to a much larger extent than any other Danish party. But they also use them in a different way. Through an analysis of press releases from a randomly chosen month in 2010, this article discusses the party's use of press releases not only as a source of information about the party's political initiatives but as a way of doing what George Lakoff has called Moral Politics. The use of press releases is then discussed in relation to the distinction presented by Lees-Marshement between product oriented, sales oriented and market oriented parties. The conclusion is that Dansk Folkeparti use the press releases as a part of their political marketing, but that the party due to its moral politics has to be classified as a sales oriented party.